2014
DOI: 10.1186/s12711-014-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Variance components for susceptibility to Mycobacterium bovis infection in dairy and beef cattle

Abstract: BackgroundInfection of livestock with bovine tuberculosis (bTB; Mycobacterium bovis) is of major economical concern in many countries; approximately 15 000 to 20 000 cattle are infected per year in Ireland. The objective of this study was to quantify the genetic variation for bTB susceptibility in Irish dairy and beef cattle.MethodsA total of 105 914 cow, 56 904 heifer and 21 872 steer single intra-dermal comparative tuberculin test records (i.e., binary trait) collected from the years 2001 to 2010 from dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…We found that heritability for bTB susceptibility was moderately high in this population and therefore selection for resistance is a feasible strategy to reduce the incidence of bTB nationwide. Other studies [1216] corroborate these findings. Tsairidou et al [13] and Bermingham et al [19], respectively reported polygenic heritabilities of 0.23 and 0.21 for susceptibility to bTB, which were similar to the estimate for phenotype 1 in our study, based on positive skin test reactors with positive post mortem examination results.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We found that heritability for bTB susceptibility was moderately high in this population and therefore selection for resistance is a feasible strategy to reduce the incidence of bTB nationwide. Other studies [1216] corroborate these findings. Tsairidou et al [13] and Bermingham et al [19], respectively reported polygenic heritabilities of 0.23 and 0.21 for susceptibility to bTB, which were similar to the estimate for phenotype 1 in our study, based on positive skin test reactors with positive post mortem examination results.…”
Section: Discussionsupporting
confidence: 66%
“…Most of earlier research on bTB was mainly focused on environmental risk factors for bTB infection [911], whilst limited attention was given towards identifying possible genetic factors in the bovine host. However, it was not until recently that genetic studies established the presence of between animal variation in dairy and beef cattle susceptibility to the disease with heritability estimates ranging between 0.09 and 0.23 [1216]. Furthermore, some genome-wide association (GWA) and regional heritability mapping (RHM) analyses aiming at identifying Quantitative Trait Loci (QTL) underlying cattle susceptibility to bTB have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, dairy breeds may have different levels of genetic resistance to M. bovis relative to beef herds (Allen et al, 2010;Richardson et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In high-frequency herds, cows are more likely to express their resistance to claw disorders. Richardson et al (2014) found a higher heritability for susceptibility to bovine tuberculosis (bTB) for herds with a higher bTB prevalence. Furthermore, Richardson et al (2014) found genetic correlations different from unity for susceptibility to bTB between environments that differed in bTB herd prevalence.…”
Section: Introductionmentioning
confidence: 98%
“…Richardson et al (2014) found a higher heritability for susceptibility to bovine tuberculosis (bTB) for herds with a higher bTB prevalence. Furthermore, Richardson et al (2014) found genetic correlations different from unity for susceptibility to bTB between environments that differed in bTB herd prevalence. Calus et al (2006) found similar results for SCS across herds with different mean bulk tank SCS.…”
Section: Introductionmentioning
confidence: 98%